Analysis of human serum glycoproteins in patients with acute coronary syndrome - Chi, Do Huu; Dung, Nguyen Tien; Dan, Pham Duc; Hai, Dang Minh; Loi, Do Doan; Nhi, Nguyen Bich; Chi, Phan Van (Academia Journal of Biology, 2013)
Acute coronary syndrome (ACS) is a health issue of great concern worldwide due to its sudden attack, high mortality rate and serious sequelae, with the number of patients increasing rapidly in both developing and developed countries. For this reason, research on diagnostic biomarkers for early diagnosis ACS is very important. Nowadays, glycoprotein has became a main research trend of proteomics. Glycosylation is a common post-translational modification, playing an important role in many processes of the body. At the same time, recent studies have shown that the glycosylated proteins are often related to pathologies of diseases: Arthritis, Alzheimer's, diabetes, leukemia, cardiovascular. Many glycoproteins identified by proteomics techniques have been currently applied as molecularly characteristic biomarkers for various diseases including acute coronary syndrome. In this study, we use two-dimensional electrophoresis technique combined with one-dimensional nano liquid chromatography connected to mass spectrometry (1D nanoLC-ESI MS / MS). Our results show that expression levels of 3 proteins, namely ceruloplasmin, haptoglobin and fibrinogen increased, and alpha-2-HS-glycoprotein had a decreased level in patient samples.